Potret Manusia Dalam Perspektif Psikologi Islam - Musripah, Musripah (Journal of Sufism and Psychotherapy, 2023)
Humans as individual creatures and as social creatures, so that in living life can never be separated from the influence of their environment. The condition of a person's thinking cannot be separated from the influence of his environment in accordance with the development of cultural, economic, political, educational and geographical factors where he lives. Therefore, to better understand the portrait of man in terms of the perspective of Islamic psychology, it is necessary to understand the essence of man and the historical background of Islamic psychology. In line with these problems, the author analyzes and studies related to "human portraits of Islamic psychology studies". With the aim of knowing how the real portrait of man in the study of Islamic psychology. The approach in this research, the author uses a qualitative library research approach. The data used uses primary and secondary data, the analysis used uses content analysis. The results showed that the holistic human portrait in the perspective of Islamic psychology provides a valuable contribution to the sciences that make humans as material objects. The interrelated nature of body, soul and spirit can be the basis of new studies both in psychology itself, and also the world of health such as holistic therapy, psychosomatic, psychoneuroimmunology (PNI), and religiopsychoneuroimmunology (RPNI).